Buoyancy Force Acting on Underground Structures considering Seepage of Confined Water. (13th January 2019) - Zhang, Ji-wen; Cao, Jie; Mu, Linlong; Wang, Le; Li, Jie
Abstract : The antifloating property of underground structures in areas with high underground water levels is a key design aspect. Evaluating the buoyancy forces acting on underground structures is complicated, particularly in the presence of confined water beneath the structures. Herein, the effects of the permeability coefficient of layered soil, hydraulic gradient, and embedment depth of the aquiclude on the buoyancy force acting on underground structures are investigated through three model tests:( 1 ) calibration of the test system, ( 2 ) buoyancy force acting on a structure located in homogeneous soil considering vertical direction seepage, and( 3 ) buoyancy force acting on a structure located in layered soil considering vertical seepage of confined water. The results show that the pore pressure along the structure and the buoyancy force acting on the underground structure considering seepage are greater than those obtained under hydrostatic conditions. The raising ratios of the pore pressure and buoyancy force are equal to the vertical hydraulic gradient when seepage occurs in homogeneous soil. In the presence of confined water, the raising ratio is significantly greater than the hydraulic gradient. In the cases studied herein, the raising ratio is approximately twice the hydraulic gradient. Simplified equations are proposed to calculate the buoyancy force acting on underground structures considering the vertical seepage of confined water. Finally, a finite element analysis is carried out to verify the conclusions obtained from the model test and the rationality of the proposed equations.